Gemcitabine plus nab-paclitaxel until progression or alternating with FOLFIRI.3, as first-line treatment for patients with metastatic pancreatic adenocarcinoma: The Federation Francophone de Cancérologie Digestive-PRODIGE 37 randomised phase II study (FIRGEMAX). (September 2020) - Rinaldi, Yves; Pointet, Anne-Laure; Khemissa Akouz, Faiza; Le Malicot, Karine; Wahiba, Bidaut; Louafi, Samy; Gratet, Alain; Miglianico, Laurent; Laharie, Hortense; Bouhier Leporrier, Karine; Thirot Bidault, Anne; Texereau, Patrick; et al.
Abstract: Background: Chemotherapy is effective in metastatic pancreatic adenocarcinoma (mPA), but new approaches are still needed to improve patients' survival and quality of life. We have previously published good efficacy and tolerability results on a sequential treatment strategy of gemcitabine followed by an intensified FOLFIRI (5FU+irinotecan) regimen. In the present study, we evaluated the same sequence but replaced gemcitabine by the new gemcitabine + nab-paclitaxel standard first-line combination. Patients and methods: We randomised chemotherapy-naive patients with proven mPA, bilirubin levels ≤1.5 upper limit of normal values and performance status 0–2 to alternately receive gemcitabine + nab-paclitaxel for 2 months then FOLFIRI.3 for 2 months in arm A, or gemcitabine + nab-paclitaxel alone until progression in arm B. The primary objective was to increase the 6-month progression-free survival (PFS) rate from 40% (H0 ) to 60% (H1 ); using the binomial exact method, 124 patients were required. Analyses were carried out in preplanned modified intention-to-treat (mITT) and per-protocol (PP) populations. Results: Between November 2015 and November 2016, 127 patients were enrolled. Main grade III–IV toxicities (% in arm A/B) were: diarrhoea (12.5/1.7), neutropenia (46.9/31, including febrile neutropenia: 1.6/0), skin toxicity (6.3/13.8), and peripheral neuropathy (6.3/8.6). No toxic deaths occurred. The objective response rate was 40.3% (95% confidence interval [CI]: 28.1–53.6) in arm A and 26.7% (95% CI: 16.1–39.7) in arm B. The primary end-point (6-month PFS rate) was 45.2% [one-sided 95% CI: 34.3–56.4] in arm A and 23.3% in arm B [one-sided 95% CI: 14.3–32.3] in the mITT population. In the PP population, median PFS and OS were 7.6 months and 6 months and 14.5 months and 12.2 months in arm A and B, respectively. Conclusions: The FIRGEMAX strategy with gemcitabine + nab-paclitaxel alternating with FOLFIRI.3 every 2 months, appears feasible and effective, with manageable toxicities, in patients able to reach >2mo of treatment. Trial registration information: EudraCT: 2014-004449-28: NCT: 0282701. Highlights: Sequential regimens every 2 months may overcome resistance to treatment in mPC. Improved oncological outcomes were seen with the predefined sequential treatment. Careful patient selection in future mPC clinical trials is of major importance.